Intrahepatic cholestasis of pregnancy: Correlation of preterm delivery with bile acids - Özlem PATA; Eser VARDARELİ and Alihan ÖZCAN and Mustafa SERTESER and İbrahim ÜNSAL and Murat SARUÇ and Cihat ÜNLÜ and Nurdan TÖZÜN (Turkish Journal of Gastroenterology, 2019)
-